The Form and Meanings of Iriak Anjai Dance Clothes in Pasaman Saiyo Art Studio - Lestari, Mia Febria; Efi, Agusti (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
One form of art is dance, dance has many types. Is one of Pasaman Regency there is Iriak Anjai dance. Along with the socio-cultural development of the user community, users increasingly do not understand their traditional arts, one of which is the Iriak Anjai dance. Therefore, the author has examined and described the components of the Iriak Anjai dance, namely its properties in the form of dance clothes in terms of the form and meaning of the Iriak Anjai dance. The method used in this research is qualitative method. This research was conducted at Pasaman Saiyo Art Studio Nagari Lundar, Panti District, Pasaman Regency. The types of data are primary data and secondary data. Data collection techniques are observation, interviews and documentation, the instrument in this research is the research himself. The data analysis technique used in data collection is the data reduction model, data presentation, and conclusion drawing. To get data validity is done trough triangulation. The results of this study found that the Iriak Anjai dance outfit at the Pasaman Saiyo Art Studio consists of absolute clothing, namely baju kurung with a design that is not too loose and pants. The complements are hood, sasamping and belt. The accessories are subang telpon and necklace. This Iriak Anjai dance suit has a function as a symbol and a meaning as the gratitude and happiness of the farmer for having obtained a satisfactory harvest.